Recycling method of sintered compact

Hydrothermal treatment and subsequent disintegration provide a method to recycle sintered zirconia bodies with thicknesses of 1 mm or more, converting them into usable powders for sintered bodies, addressing the challenges of high mechanical strength and density.

JP2025059037APending Publication Date: 2025-04-09TOSOH CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024166317
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-09-25
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Sintered zirconia bodies with thicknesses of 1 mm or more are difficult to powderize through grinding due to their high mechanical strength and density, leading to inefficient energy use and contamination with impurities.

Method used

The application of hydrothermal treatment under specific conditions, including temperatures between 150°C and 400°C and a water-to-sintered body mass ratio of 1.5 or less, followed by disintegration of the treated sintered body, enables the conversion of sintered zirconia into a recyclable powder.

Benefits of technology

This method effectively disintegrates sintered zirconia bodies into powders with a BET specific surface area of 0.5 m²/g or more and a median diameter of 0.2 μm to 2.0 μm, which can be reused as raw materials for sintered bodies, overcoming the limitations of existing recycling methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059037000001_ABST
    Figure 2025059037000001_ABST
Patent Text Reader

Abstract

To provide: a method for recycling a zirconia sintered compact, which allows the zirconia sintered compact difficult to be pulverized by grinding to be recycled; a powder obtained using the method; and at least one of uses of the powder.SOLUTION: There is provided a method for recycling a sintered compact of zirconia into a zirconia powder composed of crystal grains, in which the powder is preferably obtained by a manufacturing method comprising: a hydrothermal treatment step of subjecting the sintered compact of zirconia to the hydrothermal treatment at a hydrothermal treatment temperature of 150°C or more and 400°C or less at a mass ratio of water to the sintered compact of 1.5 or less; and a crushing step of crushing the sintered compact after the hydrothermal treatment.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to recycling of zirconia sintered bodies, and further to the recycled zirconia obtained thereby. [Background technology]

[0002] In recent years, there has been a demand for the regeneration and reuse of resources from the perspective of the Sustainable Development Goals (SDGs). However, zirconia (zirconium dioxide, ZrO 2 Ceramics such as zirconia have very high mechanical properties and chemical stability, making them very difficult to recycle. For this reason, only a portion of used ceramics (sintered bodies) is used as a cement raw material, and the majority is disposed of as waste. On the other hand, the recycling of zirconia sintered bodies has been under consideration for some time.

[0003] For example, Patent Document 1 discloses a method of crushing and pulverizing a sheet-shaped zirconia sintered body and recycling it as a sintered body raw material. Furthermore, Patent Document 2 proposes a method of recycling the sintered body by heat-treating the zirconia sintered body with water to turn the zirconia into a sol. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-263157 A [Patent Document 2] Japanese Patent Application Publication No. 10-218662 Summary of the Invention [Problem to be solved by the invention]

[0005] Zirconia sintered bodies are generally dense, and because of their high mechanical strength, it is very difficult to pulverize them by grinding. As disclosed in Patent Document 1, grinding a three-dimensional sintered body with a size or thickness of 1 mm or more is energy inefficient, and impurities are mixed in by grinding. Therefore, the method of Patent Document 1 could only be applied to extremely thin zirconia sintered bodies with a thickness of less than 1 mm. In addition, the recycling specifically disclosed in Patent Document 1 was only the recycling of a sheet-like sintered body of cubic zirconia with a thickness of less than 300 μm and low mechanical strength. In addition, Patent Document 2 states that the crystal particles constituting the zirconia ball are dissolved to obtain a fine sol, which is then molded and sintered. However, Patent Document 2 does not disclose any specific data such as observation diagrams or X-ray diffraction patterns. Furthermore, the present inventors have examined the method of Patent Document 2 and confirmed that not only is a sol not obtained, but the properties of the zirconia ball do not change at all before and after the treatment. Therefore, the zirconia sintered body could not be recycled by the method of Patent Document 2.

[0006] An object of the present disclosure is to provide a method for recycling a zirconia sintered body, which enables recycling of a zirconia sintered body that is difficult to powder by pulverization, and to provide at least one of the powder obtained by the method and uses thereof. [Means for solving the problem]

[0007] In this disclosure, we have investigated the recycling of zirconia sintered bodies having a thickness of 1 mm or more, which was considered difficult to pulverize by crushing. As a result, we have found that it is possible to crush and pulverize the sintered bodies by subjecting them to hydrothermal treatment under specific conditions. Furthermore, we have found that the powder obtained by this process can be recycled as a raw material for sintered bodies.

[0008] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] Zirconia powder consisting of crystalline particles. [2] BET specific surface area is 0.5m 2 / g or more 10.5m 2 / g or less and a median diameter of 0.2 μm or more and 2.0 μm or less. [3] The powder according to the above [1] or [2], wherein the zirconia is zirconia containing a stabilizing element. [4] The powder according to [3] above, wherein the stabilizing element is one or more selected from the group consisting of yttrium, magnesium, calcium, cerium, gadolinium and erbium. [5] The powder according to [3] or [4] above, wherein the content of the stabilizing element is 1.5 mol% or more and 6 mol% or less. [6] The powder according to any one of [1] to [5] above, having a monoclinic rate of 50% or more. [7] The BET specific surface area for the median diameter is 12 m 2 The powder according to any one of the above [1] to [6], wherein the powder has a particle size of 1 / (g·μm) or less. [8] The powder according to any one of [1] to [7] above, wherein the powder is a recycled powder. [9] A method for producing the powder according to any one of [1] to [8], comprising: a hydrothermal treatment step of hydrothermally treating a zirconia sintered body at a hydrothermal treatment temperature of 150°C or higher and 400°C or lower, with a mass ratio of water to the sintered body of 1.5 or less; and a crushing step of crushing the sintered body after the hydrothermal treatment.

[10] The method according to the above [9], wherein the zirconia sintered body is a sintered body having tetragonal zirconia as a main phase.

[11] The method according to the above [9] or

[10] , wherein the proportion of monoclinic crystals in the crystal phase of the zirconia sintered body is 5% or less.

[12] The method according to any one of [9] to

[11] above, wherein the three-point bending strength of the zirconia sintered body is 1000 MPa or more.

[13] A method for recycling sintered bodies, comprising: a hydrothermal treatment step of hydrothermally treating a zirconia sintered body at a hydrothermal treatment temperature of 150°C or higher and 400°C or lower, with a mass ratio of water to the sintered body of 1.5 or less; and a crushing step of crushing the sintered body after the hydrothermal treatment. Effect of the Invention

[0009] The present disclosure can provide at least one of a method for recycling a zirconia sintered body, which enables recycling of a zirconia sintered body that is difficult to powder by pulverization, the powder obtained thereby, and uses thereof. [Brief description of the drawings]

[0010] [Figure 1] SEM observation of the sintered body of Synthesis Example 1 (scale in the figure is 1 μm) [Diagram 2] Optical microscope observation of sintered body flakes of Example 1 (scale in the figure is 1000 μm) [Diagram 3] SEM observation image of the powder of Example 1 (scale in the figure is 1 μm) [Figure 4] SEM observation of the powder of Example 2 (scale in the figure is 1 μm) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The sintered body of the present disclosure will be described below with reference to an example of the embodiment. The terms in this embodiment are as follows. In addition, in the present disclosure, the configurations and parameters disclosed in this specification include any combination, and the upper and lower limits of the values ​​disclosed in this specification include any combination.

[0012] The "composition" is a substance having a certain composition, and examples thereof include one or more selected from the group consisting of powder, granules, a molded body, a calcined body, and a sintered body.

[0013] The term "powder" refers to a composition that is an aggregate of powder particles and has flowability. The term "zirconia powder" refers to a powder that is essentially composed of zirconia and has zirconia as the main component.

[0014] A "molded body" is a composition having a certain shape composed of powder particles aggregated by physical force, and in particular, a composition in a state in which no heat treatment has been performed after the shape has been imparted (e.g., after molding). A "zirconia molded body" is a molded body essentially made of zirconia, and further, a molded body having zirconia as a matrix (base material). In this embodiment, the terms "molded body" and "compressed powder" are used interchangeably.

[0015] The term "sintered body" refers to a composition having a certain shape composed of crystal grains, and is a composition in a state in which it has been heat-treated at a temperature equal to or higher than the sintering temperature. The shape of the sintered body of this embodiment may be at least one selected from the group consisting of spherical, approximately spherical, elliptical, disk-like, cylindrical, cubic, rectangular, polyhedral, and approximately polyhedral. Furthermore, any shape may be used to achieve a specific purpose, such as various applications. The term "zirconia sintered body" refers to a sintered body essentially made of zirconia, and further to a sintered body having zirconia as a matrix (base material).

[0016] The term "stabilizing element" refers to an element that has the function of stabilizing the crystal phase of zirconia by dissolving in zirconia.

[0017] The "BET specific surface area" is a value measured by a BET multipoint method (5 points) using nitrogen as the adsorption gas in accordance with JIS R 1626. Specific measurement conditions for the BET specific surface area include the following conditions. Adsorption medium:N 2 Adsorption temperature: -196℃ Pretreatment conditions: Degassing in air at 250℃ for 1 hour or more

[0018] The BET specific surface area can be measured using a common device (for example, Tristar II 3202, manufactured by Shimadzu Corporation).

[0019] The "median size" and "volume average size" are the particle sizes (D 50The "standard deviation" is an index that indicates the width of the particle size distribution, and is the particle size (D 16 ), and the particle size corresponding to an accumulated frequency of 84% (D 84 ) is the value calculated using the following formula: Standard deviation [μm]=(D 84 [μm]-D 16 [μm]) / 2

[0020] The volumetric particle size distribution measurement by the laser diffraction / scattering method may be performed using a general particle size distribution measuring device (for example, device name: MT-3300EXII, manufactured by Microtrack Bell) under the following conditions. Measurement range: 0.01~2000μm Particle refractive index: 2.17 Particle permeability: permeation Particle shape: non-spherical Solvent refractive index: 1.333 Calculation mode: HRA Measurement time: 30 seconds Distribution: Volume

[0021] The "monoclinic crystal ratio" is the ratio of monoclinic crystals to the total crystal phase, and is a value calculated from an X-ray diffraction (hereinafter also referred to as "XRD") pattern using the following formula.

[0022] f M =100×[I m (111)+I m (11-1)] / [I m (111)+I m (11-1)+I t (111)+I c (111)] In the above formula, f M is the monoclinic fraction, I t (111) is the surface intensity of the tetragonal (111) plane, I c (111) is the surface intensity of the cubic (111) plane, I m (111) is the surface intensity of the monoclinic (111) plane, I m(11-1) is the area intensity of the monoclinic (11-1) plane.

[0023] The intensity distribution of each crystal plane can be determined by profile fitting the XRD pattern after smoothing and background removal using a divided pseudo-Voigt function. The analysis of the XRD pattern, such as smoothing, background processing, and calculation of the intensity distribution, can be performed using an analysis program attached to the X-ray diffractometer (e.g., Integrated Powder X-ray Analysis Software PDXL Ver.2.2, manufactured by RIGAKU Corporation).

[0024] The XRD pattern in this embodiment is preferably obtained by XRD measurement under the following conditions. Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 2° / min Measurement range: 2θ=26°~33° Acceleration voltage / current: 40mA / 40kV Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter Goniometer radius: 185mm

[0025] The XRD measurement can be performed using a general X-ray diffractometer (e.g., Ultima IV, manufactured by RIGAKU Corporation). When the composition is a calcined body or a sintered body, the surface of the composition can be polished to a surface roughness Ra≦0.02 μm, and the XRD measurement can be performed on the surface.

[0026] Examples of XRD peaks corresponding to each crystal plane of zirconia measured in the above-mentioned XRD measurement include XRD peaks having peak tops at the following 2θ.

[0027] XRD peak corresponding to monoclinic (111) plane: 2θ=31±0.5° XRD peak corresponding to monoclinic (11-1) plane: 2θ=28±0.5° XRD peak corresponding to tetragonal (111) plane: 2θ=30±0.5° XRD peak corresponding to cubic (111) plane: 2θ=30±0.5° The XRD peak corresponding to the tetragonal (111) plane and the XRD peak corresponding to the cubic (111) plane are measured as a single overlapping peak. Therefore, I t (111)+I c (111) can be determined from the integrated intensity of one XRD peak having a peak top at 2θ=30±0.5°.

[0028] The "three-point bending strength" is a value determined by a three-point bending test in accordance with JIS R 1601. The measurement may be performed using a columnar sintered body sample with a width of 4 mm and a thickness of 3 mm, with a support distance of 30 mm. The three-point bending strength in this embodiment may be determined as an average value of 10 measurements.

[0029] "Normal pressure sintering" is a method of sintering by heating the material to be sintered (such as a compact or calcined body) without applying an external force.

[0030] [Powder] The present embodiment is a zirconia powder, which is a zirconia powder composed of crystal grains. The crystal grains are zirconia particles heat-treated at a temperature equal to or higher than the sintering temperature, and are zirconia particles constituting a sintered body. The sintered body is composed of crystal grains, and is a composition having a certain shape by forming grain boundaries (interfaces) between the crystal grains. In contrast, the powder of the present embodiment is a powder in a state in which the crystal grains constituting the sintered body are dispersed. In other words, the powder of the present embodiment is a powder obtained by peeling off the interfaces (grain boundaries) between the crystal grains constituting the sintered body. Note that the crystal grains can be dispersed even if the grain boundaries are not completely eliminated. Therefore, the powder of the present embodiment may contain particles having grain boundaries. The powder of the present embodiment may be regarded as a powder having crystal grains as powder particles, or a powder (sintered powder) composed of sintered particles.

[0031] Other aspects of the powder of the present embodiment include a powder in a state where a zirconia sintered body is crushed, a powder in a state where a zirconia sintered body is hydrothermally treated and crushed, and a powder in a state obtained by the method for producing a powder of the present embodiment described later.

[0032] Such powder can be obtained by reprocessing the sintered body, that is, by recycling the sintered body, and therefore the powder of this embodiment can be regarded as a recycled powder (recycled zirconia powder).

[0033] The zirconia powder used industrially is a powder obtained by a liquid phase method such as a coprecipitation method or a hydrolysis method (hereinafter, for convenience, it is also referred to as "synthetic powder"). The synthetic powder is a powder consisting of fine primary particles or secondary particles which are aggregates thereof, since it is synthesized without undergoing a thermal history at or above the sintering temperature. The synthetic powder is composed of particles in a state in which many voids are included, and the specific surface area relative to the particle diameter is larger than that of the powder of this embodiment. For example, a synthetic powder having a particle diameter similar to that of the powder of this embodiment has a high BET specific surface area, and conversely, a synthetic powder having a low specific surface area has a large particle diameter. In contrast, the powder of this embodiment is a powder in a state in which the crystal particles constituting the sintered body are dispersed. Therefore, it is considered that the individual particles (crystal particles) constituting the powder of this embodiment are dense, and the specific surface area relative to the particle diameter is small. As a result, it is considered that the powder of this embodiment has both a large particle diameter and a low specific surface area compared to the synthetic powder. In addition, the powder particles (crystal particles) constituting the powder of this embodiment may contain polyhedral particles, in contrast to the synthetic powder having an approximately spherical or other irregular shape. Therefore, the powder of this embodiment may contain polyhedral powder particles (crystal particles), or may even be made up of polyhedral powder particles.

[0034] The powder of this embodiment is a zirconia powder, and is a powder containing zirconia as a main component (so-called zirconia powder). The zirconia is preferably zirconia containing a stabilizing element (stabilized zirconia).

[0035] The stabilizing element may be any element that stabilizes the zirconia crystal phase, and may be one or more selected from the group consisting of yttrium (Y), magnesium (Mg), calcium (Ca), cerium (Ce), gadolinium (Gd) and erbium (Er). Preferably, the stabilizing element is one or more selected from the group consisting of yttrium, magnesium, calcium, gadolinium and erbium, and more preferably, at least one of yttrium and gadolinium. The powder of this embodiment is preferably obtained from a sintered body having tetragonal zirconia as the main phase, and the stabilizing element includes yttrium, and more preferably, is only yttrium.

[0036] The content of the stabilizing element (hereinafter also referred to as "stabilizing element amount", and when the stabilizing element is yttrium, etc., also referred to as "yttrium amount") may be an amount that stabilizes the crystal phase of zirconia to at least one of tetragonal and cubic, and can be exemplified as 1 mol% to 10 mol%, and further 1.6 mol% to 4.5 mol%. In order to obtain a sintered body having a tetragonal main phase, a preferred yttrium amount is 1.5 mol% or more, 2 mol% or more, or 2.5 mol% or more, and also less than 6 mol%, 5.5 mol% or less, or 3.8 mol% or less, and 1.5 mol% or more and less than 6 mol%, 2 mol% or more and 5.5 mol% or less, or 2.5 mol% or more and 3.8 mol% or less are preferred.

[0037] The amount of stabilizing element is the ratio [mol%] of the content [mol] of the stabilizing element converted into oxide to the total content [mol] of zirconia and the stabilizing element converted into oxide. 2 O 3 , magnesium is MgO, calcium is CaO, and cerium is CeO 2 , gadolinium is Gd 2 O 3 and erbium is Er 2 O 3 It is.

[0038] The powder of this embodiment may contain one or more elements selected from the group consisting of alumina, silica, and germania (hereinafter, also referred to as "additive components"). The additive component is preferably alumina.

[0039] The content of the additive component (hereinafter also referred to as "additive component amount", and when the additive component is alumina, etc., also referred to as "alumina amount", etc.) is 0% by mass or more, more than 0% by mass, or 0.01% by mass or more, and can be 0.5% by mass or less, 0.3% by mass or less, 0.1% by mass or less, or 0.75% by mass or less, and can be 0% by mass or more and 0.75% by mass or less, more than 0% by mass and 0.75% by mass or less, or 0.01% by mass or more and 0.5% by mass or less. Since it is highly versatile and can be easily mixed with various synthetic powders, it is preferable that the powder of this embodiment does not contain an additive component (additive component amount is 0% by mass), and for the same reason, it is more preferable that it does not contain at least silica. As the silica amount of the powder of this embodiment taking into account measurement errors, etc., it can be 0% by mass or more and 0.01% by mass or less, and further 0% by mass or more and 0.005% by mass or less. The amount of the added components in the powder of this embodiment can be, for example, 0% by mass or more and 0.3% by mass or less, 0% by mass or more and 0.2% by mass or less, 0% by mass or more and 0.1% by mass or less, or 0% by mass or more and less than 0.05% by mass.

[0040] The amount of the additive component in this embodiment is the ratio [mass %] of the content [g] of the additive component calculated as an oxide to the total content [g] of zirconia and the metal element calculated as an oxide (hereinafter, also referred to as the "metal amount"). 2 O 3 , silica is SiO 2 and Germania is Ge 2 O 3 It is.

[0041] The powder of the present embodiment preferably does not contain impurities, but may contain impurities within a range that does not impair the effect of the powder. In particular, the powder of the present embodiment does not contain hafnia (HfO 2 In this embodiment, the calculation of values ​​derived from the composition, such as density, may include hafnia (HfO 2 ) to zirconia (ZrO 2 ) and calculate these values.

[0042] For example, when the powder of this embodiment is a powder consisting of crystal particles of zirconia containing alumina and stabilized with yttria, the composition can be determined as follows. Metal amount [g] =ZrO 2 +Y 2 O 3 +Al 2 O 3 Alumina content [mass%] ={Al 2 O 3 / (ZrO 2 +Y 2 O 3 +Al 2 O 3 )}×100 Amount of stabilizing element (= amount of yttrium) [mol%] ={Y 2 O 3 / (ZrO 2 +Y 2 O 3 )}×100

[0043] The powder of the present embodiment is preferably a zirconia powder containing monoclinic crystals in the crystal phase, and is preferably a zirconia powder having monoclinic crystals as the main phase. The monoclinic crystal ratio of the powder of the present embodiment is more than 50%, 70% or more, or 75% or more, and may be less than 100%, 98% or less, 85% or less, or 82% or less, and is preferably more than 50% and less than 100%, 70% or more, 98% or less, 75% or more, 85% or less, or 75% or more, 82% or less. On the other hand, the monoclinic crystal ratio may be 86% or more and less than 100%, or 90% or more, 99% or less. Although cubic zirconia does not undergo a change in crystal phase due to an external force such as crushing, tetragonal zirconia undergoes a phase transition due to an external force such as crushing, and monoclinic zirconia is generated. The monoclinic crystals in the powder of this embodiment are preferably a crystal phase generated by a phase transition of a tetragonal crystal, and the powder of this embodiment is particularly preferably a zirconia powder obtained from a zirconia sintered body containing tetragonal zirconia.

[0044] The median diameter of the powder of this embodiment is preferably 0.2 μm or more and 2.0 μm or less. When the median diameter is 0.2 μm or more, the aggregation of powder particles is further suppressed. On the other hand, when the median diameter is 2.0 μm or less, the density of the sintered body obtained from the powder is likely to be high. The median diameter of the powder of this embodiment is more than 0.2 μm, 0.4 μm or more, 0.5 μm or more, or 0.7 μm or more, and may be 1.5 μm or less, 1.0 μm or less, or 0.8 μm or less, and is preferably 0.2 μm or more and 1.5 μm or less, more than 0.2 μm and 1.5 μm or less, 0.4 μm or more and 1.5 μm or less, or 0.7 μm or more and 0.8 μm or less.

[0045] The powder of this embodiment preferably has particles that are uniformly distributed, and the volume average diameter [μm] to the median diameter [μm] (hereinafter also referred to as the "particle diameter ratio") is preferably 0.9 to 1.5, and more preferably 0.95 to 1.1. The volume average diameter is one of the indicators that indicate the particle diameter of powder particles in a dispersed state, and the powder of this embodiment preferably has a volume average diameter that is approximately the same as the median diameter if it satisfies the above particle diameter ratio, for example, 0.2 μm or more, more than 0.2 μm to 0.4 μm or more, 0.5 μm or more, or 0.7 μm or more, and also 2.0 μm or less, 1.5 μm or less, 1.0 μm or less, or 0.8 μm or less, and preferably 0.2 μm to 1.5 μm, more than 0.2 μm to 1.5 μm, 0.4 μm to 1.5 μm, or 0.7 μm to 0.8 μm. The volume average diameter is preferably larger than the median diameter.

[0046] The powder of this embodiment preferably has a narrow particle size distribution, and the absolute value of the standard deviation is preferably 0.5 μm or less, 0.25 μm or less, or 0.2 μm or less. The standard deviation is preferably small, and ideally 0 μm. However, in reality, the distribution has a width, so the absolute value of the standard deviation can be more than 0 μm or more than 0.05 μm, and examples of such values ​​include more than 0 μm and less than 0.5 μm, 0.05 μm or more and less than 0.25 μm, or 0.05 μm or more and less than 0.2 μm.

[0047] The powder of this embodiment has a BET specific surface area of ​​0.5 m 2 / g or more 10.5m 2 / g or less, and 0.5m 2 / g or more 10m 2 / g or less. Although the powder of this embodiment has a relatively large particle size, the BET specific surface area is low. The BET specific surface area of ​​the powder of this embodiment is preferably 1 m 2 / g or more, more than 2m 2 / g or more or 3m 2 / g or more, and 2 / g or less, 5m 2 / g or less or 4m 2 / g or less, and 0.5m 2 / g or more 8m 2 / g or less, 2m 2 / g or more 8m 2 / g or less, or 2m 2 / g or more 4m 2 / g or less is preferable.

[0048] The powder of the present embodiment preferably has both a large particle size and a low specific surface area, and the ratio of the BET specific surface area [m 2 / g] (hereinafter referred to as the "BET ratio") is 12m 2 / (g·μm) or less, 9.5m 2 / (g·μm) or less or 5m 2 / (g·μm) or less, and 0m 2 / (g·μm) or more, 0m 2 / (g·μm) or over 2m 2 / (g·μm) or more, and 0m 2 / (g·μm) or more 12m 2 / (g·μm) or less, 0m 2 / (g·μm)Ultra 9.5m 2 / (g·μm) or less or 2m 2 / (g·μm) super 5m 2 For example, it can be exemplified as being less than or equal to / (g μm).

[0049] [Powder composition] The powder of the present embodiment may be used as a raw material for a sintered body as it is, but is also suitable as a raw material for a powder composition containing the powder and a synthetic powder (hereinafter, also referred to as "powder composition of the present embodiment"). Furthermore, the powder composition of the present embodiment may be used as a raw material for a sintered body.

[0050] The powder composition of the present embodiment may contain the above-mentioned powder of the present embodiment and any synthetic powder. For example, the powder composition of the present embodiment may contain two or more types of powder, and the powder is at least the powder of the present embodiment, and the BET specific surface area (BET ratio) relative to the median diameter is 9.5 m 2 In another embodiment, the powder composition of the present embodiment includes the powder of the present embodiment and a powder composition having a BET specific surface area relative to the median diameter of 12 m 2 A powder composition containing the powder of the present embodiment and a zirconia powder having a BET ratio of 12m 2 / (g·μm) or more, and the BET ratio is 9.5m 2 Powder compositions having a particle size of more than 1 / (g μm) are also included.

[0051] The powder composition of this embodiment may have a composition similar to that of the powder of this embodiment, and is a powder composition of zirconia, and the zirconia is preferably zirconia containing a stabilizing element.

[0052] The stabilizing element may be any element that stabilizes the crystal phase of zirconia, and examples thereof include one or more selected from the group consisting of yttrium, magnesium, calcium, cerium, gadolinium, and erbium. Preferably, the stabilizing element is one or more selected from the group consisting of yttrium, magnesium, calcium, gadolinium, and erbium, and more preferably, at least one of gadolinium and yttrium. It is preferable that the stabilizing element contains yttrium, and more preferably, the stabilizing element is only yttrium.

[0053] The amount of the stabilizing element may be an amount that stabilizes the crystal phase of zirconia in at least one of tetragonal and cubic, and may be 1 mol% or more and 10 mol% or less, or further 1.6 mol% or less and 4.5 mol% or less. In order to be suitable as a raw material for a sintered body having higher mechanical properties, the preferred amount of yttrium is 1.5 mol% or more, 2 mol% or more, or 2.5 mol% or more, and also less than 6 mol%, 5.5 mol% or less, or 3.8 mol% or less, and 1.5 mol% or more and less than 6 mol%, 2 mol% or more and 5.5 mol% or less, or 2.5 mol% or more and 3.8 mol% or less is preferred.

[0054] The powder composition of the present embodiment may contain an additive component, and the additive component is preferably alumina. The amount of the additive component is 0% by mass or more, more than 0% by mass or more than 0.01% by mass, and may be 0.5% by mass or less, 0.1% by mass or less, or 0.75% by mass or less, and may be 0% by mass or more and 0.75% by mass or less, more than 0% by mass or more and 0.75% by mass or less, or 0.01% by mass or more and 0.5% by mass or less.

[0055] The BET ratio of the powder composition of this embodiment varies depending on the amount of the synthetic powder. 2 / (g·μm) and is 9.5m 2 / (g·μm) or more 15.0m 2 / (g·μm) or less, 9.5m 2 / (g·μm) or more 13.5m 2 / (g·μm) or less or 10.0m 2 / (g·μm) or more 15.0m 2 For example, it can be exemplified as being less than or equal to / (g μm).

[0056] The powder composition of the present embodiment, if it has the above-mentioned BET ratio, exhibits moldability and sinterability similar to that of a synthetic powder, and can be used as a raw material for a sintered body. Therefore, the particle size and specific surface area may be any desired value.

[0057] The BET specific surface area of ​​the powder composition of this embodiment is 5 m 2 / g or more or 6m2 / g or more, and 2 / g or less or 8m 2 / g or less, and 2 / g or more 10m 2 / g or less, or 6m 2 / g or more 8m 2 / g or less.

[0058] The median diameter of the powder composition of this embodiment is, for example, 0.4 μm or more, 0.5 μm or more, or 0.6 μm or more, and 1.0 μm or less, 0.8 μm or less, or 0.7 μm or less, such as 0.4 μm or more to 1.0 μm or less, 0.5 μm or more to 0.8 μm or less, or 0.6 μm or more to 0.7 μm or less.

[0059] The particle size ratio of the powder composition of this embodiment may be 0.9 or more and 1.5 or less, and further 0.95 or more and 1.1 or less. The volume average diameter of the powder composition of this embodiment may be approximately the same as the median diameter, and may be, for example, 0.4 μm or more or 0.5 μm or more, and 1.0 μm or less or 0.8 μm or less, and is preferably 0.4 μm or more and 1.0 μm or less, or 0.5 μm or more and 0.8 μm or less. The volume average diameter is preferably larger than the median diameter.

[0060] The absolute value of the standard deviation of the powder composition of this embodiment is 0.2 μm or less, or 0.18 μm or less, and can be greater than 0 μm or greater than 0.05 μm, for example greater than 0 μm and less than 0.2 μm, or greater than 0.05 μm and less than 0.18 μm.

[0061] The monoclinic ratio of the powder composition of this embodiment is 25% or more, or 40% or more, and can be 60% or less, or 50% or less, for example, 25% or more and 60% or less, or 40% or more and 50% or less.

[0062] As long as the powder composition has these configurations, the content ratio of the powder of this embodiment and the synthetic powder is arbitrary, but it is preferable that the mass ratio of the synthetic powder in the powder composition of this embodiment is 0.2 or more, 0.3 or more, or 0.5 or more, and also less than 1.0, 0.9 or less, or 0.8 or less, and further examples thereof include 0.2 or more and less than 1.0, 0.3 or more and 0.9 or less, 0.5 or more and 0.9 or less, or 0.5 or more and 0.8 or less.

[0063] The powder composition of this embodiment is a powder of this embodiment and a powder having a BET specific surface area relative to the median diameter of 12 m 2 The powder is then mixed with zirconia powder having a BET ratio of 12m / (g·μm). 2 The zirconia powder having a surface roughness of more than 1 / (g·μm) (hereinafter also referred to as “additive powder”) may be a synthetic powder or even a commercially available zirconia powder.

[0064] The mass proportion [mass %] of the powder of this embodiment in the powder composition of this embodiment is arbitrary, but it may be such that, with the total of the additive powder and the powder of this embodiment being 100 mass %, the powder of this embodiment accounts for 5 mass % or more, 10 mass % or more, 30 mass % or more, or 50 mass % or more.

[0065] The mixing in the mixing step may be performed in any manner that makes the additive powder and the powder of the present embodiment homogenous, and is at least one of wet mixing and dry mixing, preferably wet mixing, more preferably either stirring mill mixing or ball mill mixing, and even more preferably ball mill mixing.

[0066] [Powder manufacturing method] The powder of this embodiment can be obtained by a production method (hereinafter also referred to as the "production method of this embodiment") that includes a hydrothermal treatment step of hydrothermally treating a zirconia sintered body at a hydrothermal treatment temperature of 150°C or more and 400°C or less, with a mass ratio of water to the sintered body of 1.5 or less, and a crushing step of crushing the sintered body after the hydrothermal treatment.

[0067] The manufacturing method of this embodiment includes a hydrothermal treatment step. The hydrothermal treatment step makes the sintered body into a solid with reduced mechanical strength (hereinafter, also referred to as "sintered body flakes" or simply "flakes"). This allows the sintered body to be subjected to the subsequent crushing step in an easier-to-handle state than a state with high fluidity such as a gel, and furthermore, crushing makes it easier for the crystal particles to disperse while maintaining their shape.

[0068] The shape and size of the sintered body flakes vary depending on the shape and size of the sintered body (hereinafter also referred to as the "raw sintered body") to be subjected to the hydrothermal treatment step. The sintered body flakes may have a maximum length of 10 mm or less, and may further have a maximum length of 5 mm or less. The shape of the sintered body flakes may be scale-like sintered body pieces, and may be at least one of a polyhedral shape and an irregular shape.

[0069] A zirconia sintered body is provided for the hydrothermal treatment step. The shape of the raw sintered body is arbitrary, and may be, for example, one or more selected from the group consisting of spherical, approximately spherical, elliptical, disk-shaped, cylindrical, cubic, rectangular, polyhedral, and approximately polyhedral. The sintered body provided for the hydrothermal treatment step may be a sintered body having a thickness of 1 mm or more, or even a sintered body having a thickness of 3 mm or more, and preferably a sintered body having a thickness of 1 mm to 10 mm, or even a sintered body having a thickness of 3 mm to 5 mm. In the manufacturing method of this embodiment, even if the sintered body has such a thickness, crystal particles can be dispersed and the sintered body can be made into a powder.

[0070] The manufacturing method of this embodiment is suitable for recycling sintered bodies that are difficult to crush. Therefore, the three-point bending strength of the raw sintered body may be 1000 MPa or more, further 1100 MPa or more, or even 1200 MPa or more. The upper limit of the three-point bending strength of the raw sintered body may be 1600 MPa or less or 1500 MPa or less. In addition, the three-point bending strength of the raw sintered body may be 1000 MPa or more and 1600 MPa or less, 1100 MPa or more and 1500 MPa or less, or 1200 MPa or more and 1500 MPa or less.

[0071] The raw material sintered body is preferably a sintered body having tetragonal zirconia as the main phase, and the proportion of monoclinic crystals in the crystal phase (monoclinic crystal ratio) is preferably 5% or less, and more preferably 3% or less, and the monoclinic crystal ratio can be 0% or more and 5% or less, 0% or more and 3% or less, or 0% or more and 2% or less.

[0072] The composition of the raw material sintered body may be the same as that of the powder of the present embodiment described above, and is a sintered body of zirconia, preferably zirconia containing a stabilizing element.

[0073] The stabilizing element may be any element that stabilizes the zirconia crystal phase, and may be one or more selected from the group consisting of yttrium, magnesium, calcium, cerium, gadolinium, and erbium. Preferably, the stabilizing element is one or more selected from the group consisting of yttrium, magnesium, calcium, gadolinium, and erbium, and more preferably, at least one of yttrium and gadolinium. It is preferable that the stabilizing element contains yttrium, or more preferably, that the stabilizing element is only yttrium.

[0074] The amount of the stabilizing element may be an amount that stabilizes the crystal phase of zirconia in at least one of tetragonal and cubic, and may be 1 mol% or more and 10 mol% or less, or further 1.6 mol% or less and 4.5 mol% or less. The preferred amount of yttrium is 1.5 mol% or more, 2 mol% or more, or 2.5 mol% or more, and less than 6 mol%, 5.5 mol% or less, or 3.8 mol% or less, and preferably 1.5 mol% or more and less than 6 mol%, 2 mol% or more and 5.5 mol% or less, or 2.5 mol% or more and 3.8 mol% or less.

[0075] The raw sintered body may contain an additive component, and the additive component is preferably alumina. The amount of the additive component is 0% by mass or more, more than 0% by mass or 0.01% by mass or more, and may be 0.5% by mass or less, 0.1% by mass or less, or 0.75% by mass or less, and may be 0% by mass or more and 0.75% by mass or less, more than 0% by mass or 0.75% by mass or less, or 0.01% by mass or more and 0.5% by mass or less. On the other hand, for the same reasons as those mentioned above, it is preferable that the raw sintered body does not contain an additive component (additive component amount is 0% by mass), and it is more preferable that it does not contain at least silica. The amount of silica of the raw sintered body taking into account measurement errors and the like may be 0% by mass or more and 0.01% by mass or less, or even 0% by mass or more and 0.005% by mass or less. The amount of the additive component of the raw sintered body may be 0% by mass or more and 0.3% by mass or less, 0% by mass or more and 0.2% by mass or less, 0% by mass or more and 0.1% by mass or less, or 0% by mass or more and less than 0.05% by mass.

[0076] The water used in the hydrothermal treatment may be pure water.

[0077] In the hydrothermal treatment step, the hydrothermal treatment is performed at a hydrothermal treatment temperature of 150°C or more and 400°C or less. If the hydrothermal treatment temperature is less than 150°C, the hydrothermal treatment takes a very long time, and the treatment cannot be performed in a practical time. On the other hand, if the hydrothermal treatment temperature exceeds 400°C, a general-purpose hydrothermal treatment device cannot be used, and the crystal particles themselves tend to collapse or dissolve. In either case, it is difficult to apply the method as an industrial recycling method. The hydrothermal treatment temperature is 150°C or more or 180°C or more, and may be 400°C or less, 350°C or less, or 300°C or less, and is preferably 150°C or more and 400°C or less, or 180°C or more and 300°C or less.

[0078] The hydrothermal treatment is carried out in a state where the sintered body and water are sealed, and therefore, the hydrothermal treatment is carried out under autogenous pressure.

[0079] In the hydrothermal treatment step, the mass ratio of water to the sintered body (hereinafter also referred to as "solid-liquid ratio") is set to 1.5 or less. In the hydrothermal treatment step, the water is vaporized by heating in a closed system and comes into contact with the sintered body. This allows the change in the sintered body to proceed moderately, and it is believed that the strength of the grain boundaries (interfaces) between the crystal particles is reduced prior to the collapse or dissolution of each crystal particle itself. This is believed to result in a state in which the crystal particles can be easily dispersed by crushing. If the solid-liquid ratio exceeds 1.5, the generation of water vapor and the contact with the sintered body become insufficient. As a result, the mechanical strength of the sintered body does not decrease, and the crystal particles cannot be dispersed in the subsequent crushing step. In order to make the interface strength of the sintered body flakes obtained by the hydrothermal treatment more uniform, it is preferable that the solid-liquid ratio is 1.5 or less, 1.0 or less, or 0.75 or less. The solid-liquid ratio may be within a range in which sufficient contact between the sintered body and water vapor occurs, and may be 0.1 or more or 0.25 or more, and is preferably 0.1 to 1.5, 0.1 to 1.0, or 0.25 to 0.57.

[0080] The hydrothermal treatment may be performed while the zirconia sintered body is stirred or left to stand, but it is preferable to perform the hydrothermal treatment while the sintered body is left to stand, since this improves the handleability of the resulting sintered body flakes.

[0081] The time for the hydrothermal treatment may be adjusted as appropriate depending on the amount of sintered body to be subjected to the hydrothermal treatment and the performance of the hydrothermal treatment apparatus. As an industrial recycling method, the time is, for example, 20 hours or more, 50 hours or more, or 70 hours or more, and 300 hours or less, 150 hours or less, 120 hours or less, or 100 hours or less, and examples thereof include 20 hours or more and 300 hours or less, or 50 hours or more and 100 hours or less.

[0082] If necessary, the sintered body (sintered body flakes) after the hydrothermal treatment may be collected by solid-liquid separation and dried. Unlike gels, the sintered body flakes are sintered body pieces of millimeter order, and solid-liquid separation is easy, so the solid-liquid separation and drying methods are optional. As a method of solid-liquid separation, at least one of decantation and filtration can be mentioned, and solid-liquid separation by filtration is preferable. As a drying method, drying in the air at 80°C or more and 150°C or less can be mentioned.

[0083] The manufacturing method of this embodiment includes a crushing step of crushing the sintered body after the hydrothermal treatment. By the crushing step, the crystal particles constituting the sintered body flakes are dispersed, and the powder of this embodiment composed of the crystal particles is obtained.

[0084] The crushing method in the crushing step may be any method and condition that can destroy the grain boundaries of the crystal particles, and may be at least one of wet crushing and dry crushing, or may be wet crushing. A preferred wet crushing method is a method in which the sintered flakes are made into a slurry and crushed. In order to increase the crushing strength, for example, zirconia balls having a diameter of 0.1 mm to 20 mm may be used for crushing. In this embodiment, "crushing" refers to a process for removing slow agglomerates, and "pulverization" refers to a process for destroying primary particles and crystal particles themselves.

[0085] Furthermore, in the crushing step, the powder composition of this embodiment can also be obtained by adding a synthetic powder when crushing the sintered body flakes.

[0086] The manufacturing method of this embodiment can be used as a recycling method for sintered bodies, a recycling method for sintered bodies, and further as a recycling method for zirconia sintered bodies, and may be regarded as a recycling method for sintered bodies having a hydrothermal treatment step of hydrothermally treating a zirconia sintered body at a hydrothermal treatment temperature of 150°C or more and 400°C or less, with a mass ratio of water to the sintered body of 1.5 or less, and a crushing step of crushing the sintered body after the hydrothermal treatment.

[0087] [Method of manufacturing sintered body] The powder of this embodiment and the powder composition of this embodiment (hereinafter also referred to as "the powder of this embodiment") can each be used as a raw material for a sintered body. The sintered body may be produced by a known sintering method other than using the powder of this embodiment, and can be produced by a production method including a sintering step of sintering a molded body containing the powder of this embodiment.

[0088] The molded body to be subjected to the sintering step may have any shape, including at least one shape selected from the group consisting of spherical, approximately spherical, elliptical, disk-like, cylindrical, cubic, rectangular, polyhedral, and approximately polyhedral shapes, or any shape according to the application or purpose.

[0089] The green body may be formed by molding the powder of the present embodiment using any molding method, such as at least one method selected from the group consisting of uniaxial pressing, cold isostatic pressing, slip casting, and injection molding, and at least one method selected from the group consisting of uniaxial pressing and cold isostatic pressing.

[0090] The sintering method in the sintering step may be any sintering method, and may be one or more selected from the group consisting of atmospheric sintering, pressure sintering, and vacuum sintering, with atmospheric sintering being preferred.

[0091] Preferred sintering conditions include the following conditions.

[0092] Sintering method: Pressureless sintering Sintering atmosphere: Oxidizing atmosphere, preferably air atmosphere Holding temperature: 1300°C or higher, 1400°C or higher, or 1450°C or higher, and 1700℃ or less or 1600℃ or less The holding time may be appropriately changed depending on the shape of the molded body to be sintered and the characteristics of the sintering furnace, but can be, for example, from 1 hour to 6 hours, or from 2 hours to 4 hours.

[0093] By passing through the sintering step, a sintered body using raw materials obtained from the sintered body, that is, a so-called recycled sintered body, can be obtained, whereby the sintered body can be recycled. EXAMPLES

[0094] The present disclosure will be described below using examples, but the present disclosure is not limited to these examples. (Crystal phase, monoclinic ratio) An XRD pattern of the sample was obtained by XRD measurement under the following conditions using an X-ray diffraction apparatus (apparatus name: Ultima IV, manufactured by RIGAKU Corporation). Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 2° / min Measurement range: 2θ=26°~33° Acceleration voltage / current: 40mA / 40kV Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter Goniometer radius: 185mm

[0095] The crystalline phases were identified by smoothing and background removal processing using an analysis program attached to the X-ray diffractometer (program name: Integrated Powder X-ray Analysis Software PDXL Ver. 2.2, manufactured by RIGAKU Corporation), and then profile fitting the processed XRD pattern using a split pseudo-Voigt function. The sintered samples used were 1.3±0.1 mm in diameter and one side of the sintered samples was mirror-polished to a measured surface roughness of Ra≦0.02 μm. The monoclinic ratio was calculated from the XRD patterns of the surfaces of the powder sample and the sintered body sample by the above formula.

[0096] (BET specific surface area) The BET specific surface area was measured by the BET multipoint method (5 points) using an automatic specific surface area measuring device (device name: Tristar II 320, manufactured by Shimadzu Corporation) in accordance with JIS R 1626 under the following conditions. Adsorption medium:N 2 Adsorption temperature: -196℃ Pretreatment conditions: Air atmosphere, degassing at 250℃ for 1 hour

[0097] (Median diameter, volume average diameter and standard deviation) The median diameter, volume average diameter and standard deviation were determined from the cumulative volume particle size distribution obtained by measuring the volumetric particle size distribution using a Microtrac particle size distribution analyzer (device name: MT3300EXII, manufactured by Microtrac Bell Co., Ltd.) by the laser diffraction / scattering method. The measurement conditions for particle size distribution are shown below. Measurement range: 0.01~2000μm Particle refractive index: 2.17 Particle permeability: permeation Particle shape: non-spherical Solvent refractive index: 1.333 Calculation mode: HRA Measurement time: 30 seconds Distribution: Volume The particle size corresponding to 50% cumulative frequency in the cumulative volume particle size distribution (D 50 The particle diameter (D diameter) corresponding to a cumulative frequency of 16% in the cumulative volume particle diameter distribution was taken as the median diameter [μm], and the average diameter in the cumulative volume particle diameter distribution was taken as the volume average diameter [μm]. 16 ), and the particle size corresponding to an accumulated frequency of 84% (D 84 ) and the value calculated from the following formula was used as the standard deviation [μm]. Standard deviation [μm]=(D 84 [μm]-D 16 [μm]) / 2 As a pretreatment, the sample powder was suspended in distilled water to form a slurry, which was then dispersed using an ultrasonic homogenizer (device name: US-150T, manufactured by Nippon Seiki Seisakusho).

[0098] (Actual density and relative density) The measured density of a sintered body is the ratio of the mass measured by gravimetry to the volume measured by Archimedes' method (g / cm 3 The relative density was calculated as the ratio (%) of the measured density to the true density. (Three-point bending strength) The three-point bending strength was measured by a three-point bending test according to JIS R 1601. The measurement was performed 10 times, and the average value was taken as the three-point bending strength. The measurement was performed using a columnar sintered body sample with a width of 4 mm and a thickness of 3 mm, with the distance between supports set to 30 mm. (Hydrothermal Deterioration Test) The sintered compacts were mirror-polished to a surface roughness of Ra≦0.02 μm and used as measurement samples. They were immersed in hot water at 134°C to carry out a hydrothermal degradation test. The monoclinic ratio of the sintered compact surface after immersion for 5 hours was calculated using the above formula.

[0099] <Preparation of sintered body> Synthesis Example 1 25 g of commercially available zirconia powder (product name: TZ-3YS, manufactured by Tosoh Corporation) was filled into a 57 mm × 34 mm mold and uniaxially pressed at 98 MPa to obtain a green body. The green body obtained was sintered under atmospheric pressure at 1500°C for 2 hours in an air atmosphere to obtain a rectangular sintered body having a thickness of 3.7 mm and made of yttrium-stabilized zirconia with an yttrium content of 3.0 mol%, which was used as the sintered body of this synthesis example.

[0100] Synthesis Example 2 A rectangular parallelepiped sintered body made of yttrium-stabilized zirconia having a thickness of 3.7 mm and an yttrium content of 2.0 mol% was obtained in the same manner as in Example 1, except that a commercially available zirconia powder (product name: TZ-2Y, manufactured by Tosoh Corporation) was used, and a zirconia sintered body was obtained.

[0101] The results are shown in the table below, and the SEM image of the sintered body of Synthesis Example 1 is shown in FIG.

[0102] [Table 1]

[0103] The monoclinic ratio of all the sintered bodies was below the measurement limit (1% or less), and it was confirmed that the sintered bodies were zirconia bodies whose main crystal phase was tetragonal zirconia.

[0104] Example 1 100 g (4 pieces) of the sintered body obtained by the same method as in Synthesis Example 1 and 50 mL of pure water were charged into a 100 mL Teflon (registered trademark) container, which was then sealed and subjected to a hydrothermal treatment under the following conditions.

[0105] Hydrothermal treatment temperature: 200℃ Hydrothermal treatment time: 72 hours Hydrothermal treatment atmosphere: Still Solvent / sintered body mass ratio: 0.5 After the hydrothermal treatment, the mixture was cooled to room temperature. After cooling, the solids were collected by solid-liquid separation through filtration. The collected solids were dried in an air atmosphere at 110°C ± 15°C for 24 hours to obtain flakes. The obtained flakes had a thickness of 0.8 mm or less and a monoclinic crystal ratio of 71%. Figure 2 shows an optical microscope image of the obtained flakes. It was confirmed that the flakes had a maximum length of 3 mm or less and were solids consisting of a scale-like or irregular shape. The obtained flakes were mixed with pure water and wet-crushed to form a slurry.

[0106] The obtained slurry was dried in an air atmosphere at 110±15° C. for 24 hours, and then classified using a stainless steel sieve with a mesh size of 180 μm. The powder that passed through the sieve was collected and used as the powder of this example.

[0107] Example 2 The flakes obtained in the same manner as in Example 1 were mixed with pure water and then crushed for 24 hours in a ball mill using zirconia balls with a diameter of 2 mm. The powder of this example was obtained in the same manner as in Example 1, except that the slurry after the treatment was dried and classified.

[0108] Example 3 Except for using the sintered body of Synthesis Example 2 and changing the hydrothermal treatment time to 48 hours, the powder of this example was obtained in the same manner as in Example 1. The obtained flakes had a thickness of 0.8 mm or less and a monoclinic rate of 96%.

[0109] Comparative Example 1 Zirconia balls with a diameter of 5 mm were hydrothermally treated by the method of Patent Document 2. That is, 100 g of 5 mm diameter balls made of partially stabilized zirconia and 200 mL of pure water were added to an autoclave with a volume of 2000 mL, and heat-treated at 200°C for 96 hours while stirring. However, although cracks were confirmed in the balls after the heat treatment, the shape before the hydrothermal treatment was maintained. From this, it was confirmed that the method of Patent Document 2 cannot be used for recycling.

[0110] The results are shown in the table below. In the table, the reference example is the measurement result of a commercially available zirconia powder (product name: TZ-3YS, manufactured by Tosoh Corporation).

[0111] [Table 2]

[0112] In Examples 1 to 3, it was confirmed that the three-point bending strength was 1000 MPa or more, and that the zirconia sintered body mainly composed of tetragonal zirconia could be powdered. In addition, from a comparison between Reference Example and Example 2, it was confirmed that the powder of the Example had a lower BET ratio and a higher monoclinic rate. Furthermore, it was confirmed that the particle diameters of the powders of Examples 1 and 2 were approximately the same, 1.14 to 1.37 times the average crystal grain size (0.51 μm) of the raw material sintered body, and that the crystal grains were dispersed.

[0113] From the SEM observation diagrams (FIGS. 3 and 4) of the powders of Examples 1 and 2, both the powders of Examples 1 and 2 contained polyhedral particles (crystal particles). From this, it was confirmed that the powders of these Examples were powders consisting of crystal particles in which the crystal particles of the sintered body were in a dispersed state while maintaining their shape. Furthermore, compared with Example 2, it was confirmed that the powder of Example 1 contained many particles consisting of multiple crystal particles. Furthermore, from the comparison between Examples 1 and 2, it was confirmed that the median diameter approached the average crystal particle size of the raw material sintered body by the ball mill, and the crystal particles were further dispersed.

[0114] <Production of Powder Composition> Example 4 The powder composition of this example was obtained in the same manner as in Example 1, except that 10 g of the flakes obtained in the same manner as in Example 1, 90 g of commercially available zirconia powder (product name: TZ-3YS, manufactured by Tosoh Corporation), and 122 g of pure water were mixed while being crushed.

[0115] Example 5 The powder composition of this example was obtained in the same manner as in Example 1, except that 20 g of the flakes obtained in the same manner as in Example 1, 80 g of commercially available zirconia powder (product name: TZ-3YS, manufactured by Tosoh Corporation), and 122 g of pure water were mixed while being crushed.

[0116] Example 6 The powder composition of this example was obtained in the same manner as in Example 1, except that 50 g of the flakes obtained in the same manner as in Example 1, 50 g of commercially available zirconia powder (product name: TZ-3YS, manufactured by Tosoh Corporation), and 122 g of pure water were mixed while being crushed.

[0117] Example 7 20 g of the powder obtained in the same manner as in Example 2, 80 g of a commercially available zirconia powder (product name: TZ-3YS, manufactured by Tosoh Corporation), and 122 g of pure water were mixed while being crushed to obtain a slurry. The obtained slurry was dried in an air atmosphere at 110±15°C for 24 hours, and then classified using a stainless steel sieve with a mesh size of 180 μm. The powder that passed through the sieve was collected and used as the powder composition of this example.

[0118] Example 8 The powder composition of this example was obtained in the same manner as in Example 7, except that 50 g of the powder obtained in the same manner as in Example 2, 50 g of a commercially available zirconia powder (product name: TZ-3YS, manufactured by Tosoh Corporation), and 122 g of pure water were mixed while being crushed to obtain a slurry.

[0119] Comparative Example 2 The powder composition of this example was obtained in the same manner as in Example 1, except that 80 g of the flakes obtained in the same manner as in Example 1, 20 g of a commercially available zirconia powder (product name: TZ-3YS, manufactured by Tosoh Corporation), and 122 g of pure water were mixed while being crushed to form a slurry.

[0120] The results are shown in the table below.

[0121] [Table 3]

[0122] <Production of sintered body> 3 g of the powder obtained in each of the examples and comparative examples was filled into a die having a diameter of 25 mm, and uniaxially pressed at a pressure of 98 MPa to obtain a molded body. The obtained molded body was sintered in a muffle furnace under the following conditions to obtain a sintered body.

[0123] Heating rate: 100℃ / hour Sintering temperature: 1500℃ Sintering time: 2 hours The results are shown in the table below.

[0124] [Table 4]

[0125] It was confirmed that the obtained recycled powder could be used as a raw material for a sintered body. In addition, in Comparative Example 2, although a sintered body was obtained, the density of the sintered body was low.

Claims

1. Zirconia powder consisting of crystalline particles.

2. BET specific surface area is 0.5m 2 / g or more 10.5m 2 2. The powder according to claim 1, having a molecular weight of 0.1 μm or more and a median diameter of 0.2 μm or more and 2.0 μm or less.

3. 3. The powder according to claim 1, wherein the zirconia contains a stabilizing element.

4. 4. The powder of claim 3, wherein the stabilizing element is one or more from the group consisting of yttrium, magnesium, calcium, cerium, gadolinium and erbium.

5. The powder according to claim 3 , wherein the content of the stabilizing element is 1.5 mol % or more and 6 mol % or less.

6. The powder according to claim 1 or 2, having a monoclinic rate of 50% or more.

7. The BET specific surface area for the median diameter is 12 m 2 The powder according to claim 1 or 2, wherein the particle size is 1 / (g·μm) or less.

8. 3. The powder according to claim 1 or 2, wherein the powder is a recycled powder.

9. 2. The method for producing the powder according to claim 1, comprising: a hydrothermal treatment step of hydrothermally treating a zirconia sintered body at a hydrothermal treatment temperature of 150° C. or more and 400° C. or less, with a mass ratio of water to the sintered body of 1.5 or less; and a crushing step of crushing the sintered body after the hydrothermal treatment.

10. The method according to claim 9, wherein the zirconia sintered body is a sintered body having tetragonal zirconia as a main phase.

11. The method according to claim 9 or 10, wherein the proportion of monoclinic crystals in the crystal phase of the zirconia sintered body is 5% or less.

12. The method according to claim 9 or 10, wherein the zirconia sintered body has a three-point bending strength of 1000 MPa or more.

13. A method for recycling a sintered body, comprising: a hydrothermal treatment step of hydrothermally treating a zirconia sintered body at a hydrothermal treatment temperature of 150°C or higher and 400°C or lower, with a mass ratio of water to the sintered body of 1.5 or less; and a crushing step of crushing the sintered body after the hydrothermal treatment.

Citation Information

Patent Citations

  • Production of zirconia sintered compact

    JP1998218662A

  • Method for producing dense zirconia sintered compact, the dense zirconia sintered compact, electrolyte for solid oxide type fuel cell using the same, and solid oxide type fuel cell

    JP2009263157A